HUBUNGAN PENGAWASAN PIMPINAN DENGAN SEMANGAT KERJA PEGAWAI BADAN PENDIDIKAN DAN PELATIHAN PROVINSI SUMATERA BARAT - Diah Novianingsih (Jurnal Bahana Manajemen Pendidikan, 2013)
The purpose of this study was to know about the supervisory leadership and employee morale, and found a significant association between two variables. The population are 60 employees and samples 38 employees, who were taken using stratifield propotional random sampling technique. The research instrument used a questionnaire with liker scale models have been tested for validity and reability. Data were analyzed using product moment correlation. The result of study are indicates quite appropriate supervisory leadership, employee morale is good, and there was a significant between the supervisory leadership of the employee morale at the Badan Pendidikan dan Pelatihan of West Sumatra Province. Kata kunci: pengawasan dan semangat kerja